Pediatric unsedated transnasal endoscopy: applications, equipment, and future directions - Bose, Paroma; Pitman, Ryan (Frontiers in Pediatrics, 2025)
Gastrointestinal (GI) endoscopy is a valuable tool to diagnose and treat GI conditions. Traditional pediatric GI endoscopy uses sedation or general anesthesia, with associated risks of cardiopulmonary compromise and social and economic costs like school or work absence. Unsedated, transnasal endoscopy is an approach that mitigates these disadvantages but provides similar diagnostic benefit to conventional endoscopy. Ongoing advances in the field of pediatric transnasal endoscopy will be driven by an enhanced understanding of current indications, available equipment, procedural comfort strategies, and recent developments in new diagnostic and therapeutic uses.